What is the Relationship between the Two Ancient Syriac Peshitta Versions of 1 Maccabees?: A New Proposal that Challenges the Classical Explanation - Carbajosa, Ignacio (Aramaic studies, 2020)
The Syriac version of 1 Macc. that is preserved in Codex Ambrosianus (7a1) is very different from the one attested in the rest of the manuscripts of the Peshitta. This double attestation is typically explained by a hypothesis first put forward by G. Schmidt in 1897 that sees the version of 7a1 (Syr-2) as a revision of the original Syriac translation (Syr-1), which is the one attested in the majority of the manuscripts. This article aims to challenge this theory. In fact, this study shows that there is no relationship between Syr-1 and Syr-2, that is, Syr-2 cannot be considered a revision of Syr-1 (intended to eliminate additions), but must be understood as a new translation made from the Greek. For its part, Syr-1 is characterised by a number of double readings that could be interpreted as the work of an editor who preserves readings from two different Syriac versions of 1 Macc.